2017
DOI: 10.1002/2017jb014721
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Sedimentary Structure Using Frequency‐Dependent P Wave Particle Motion: A Case Study of the Songliao Basin in NE China

Abstract: Knowledge on sedimentary structure within a basin is of great importance for exploring petroleum resources and predicting strong ground motions caused by earthquakes. Although 3‐D seismic data acquisition is common nowadays in petroleum industry, it is still impossible to conduct dense 3‐D seismic surveys at a whole‐basin scale. Passive seismic imaging thus can play a significant role in obtaining large‐scale sedimentary structure of basins with a reasonably good resolution. Here we present a new method to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…This horizontal P wave delay results from the interference of the direct P wave with P ‐to‐ S conversion at the sediment base and sediment reverberations. Bao and Niu () found that the horizontal P wave delay time is a function of frequency and used this frequency‐dependent delay time to constraint the S wave velocity and thickness of the sediment. In this study, instead of using the frequency‐dependent delay times of the teleseismic P wave to constrain the thickness of sedimentary basins, we employ the cross‐convolution misfit function (Bodin et al, ; Menke & Levin, ) as part of the objective function in the joint inversion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This horizontal P wave delay results from the interference of the direct P wave with P ‐to‐ S conversion at the sediment base and sediment reverberations. Bao and Niu () found that the horizontal P wave delay time is a function of frequency and used this frequency‐dependent delay time to constraint the S wave velocity and thickness of the sediment. In this study, instead of using the frequency‐dependent delay times of the teleseismic P wave to constrain the thickness of sedimentary basins, we employ the cross‐convolution misfit function (Bodin et al, ; Menke & Levin, ) as part of the objective function in the joint inversion.…”
Section: Methodsmentioning
confidence: 99%
“…Bao and Niu (2017) found that the horizontal P wave delay time is a function of frequency and used this frequency-dependent delay time to constraint the S wave velocity and thickness of the sediment. This horizontal P wave delay results from the interference of the direct P wave with P-to-S conversion at the sediment base and sediment reverberations.…”
Section: Apparent Horizontal P Wave Time Delays and The Cross-convolumentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by the spatial variability of site amplification shown in Figures 3 and 4, the areas with substantial amplification are strongly correlated with sedimentary structures. These basins are filled with unconsolidated sediments up to 4 km in thickness (Bao & Niu, 2017;Li et al, 2016). The low-velocity shallow deposits resting on metamorphic basement create a strong contrast in near-surface material properties and thus substantially shown for reference (magenta lines).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the arrival time of teleseismic P-waves recorded inside a sedimentary basin displays time delays and polarization that both strongly depend on the basin properties and topography (e.g. Schmandt and Clayton 2013;Hofstetter and Dorbath 2014;Bao and Niu 2017).…”
Section: Introductionmentioning
confidence: 99%